Novel Visualizations and Interactions for Social Networks Exploration - Henry Riche, Nathalie; Fekete, Jean-Daniel (Handbook of Social Network Technologies and Applications, 2010)
In the last decade, the popularity of social networking applications has dramatically increased. Social networks are collection of persons or organizations connected by relations. Members of Facebook listed as friends or persons connected by family ties in genealogical trees are examples of social networks. Today's web surfers are often part of many online social networks: they communicate in groups or forums on topics of interests, exchange emails with their friends and colleagues, express their ideas on public blogs, share videos on YouTube, exchange and comment photos on Flickr, participate to the edition of the online encyclopedia Wikipedia or contribute to daily news by collaborating to Wikinews or Agoravox.